Complete mitochondrial genome of the glowbelly Acropoma japonicum (Perciformes: Acropomatidae) in the East China Sea. Issue 2 (3rd July 2019) - Sui, Yanming; Wu, Yanqing; Yang, Liguo; Sheng, Wenquan; Zhang, Bianbian
Abstract: The complete mitochondrial genome sequence of Acropoma japonicum is first described in this article. The total length of mitogenome is16, 973 bp. It contains 13 protein-coding genes, 23 tRNA genes, and 2 ribosomal RNA genes. The overall base composition of H-strand is 27.64% A, 29.49% C, 26.84% T, and 16.03% G, with an A＋T bias of 54.48%. The phylogenetic analysis result showed that the A. japonicum and Lutjanus peru had a close relationship.